Factory layout at WH furniture & works sdn. bhd: an application of flow diagram and process chart/ Azfawani Hj Mohd Azami, Hamizah Jamhari& Mohamad Norjayadi Tamam - Hj Mohd Azami, Azfawani; Jamhari, Hamizah; Tamam, Mohamad Norjayadi (2010)
This chapter provides an introduction to the applied business project. It first illustrates on an overview of the background of study which explained in general the furniture industry in Malaysia. Then it covers the background of the company in brief and later specifies the problem statement which leads to the research objectives and questions, scope of study, significance of study and finally the limitation that we encountered when conducting this study. Lastly this chapter elaborated on the main definition of our study.